New knowledge of the mechanisms of sorafenib resistance in liver cancer - Zhu, Yan-jing; Zheng, Bo; Wang, Hong-yang; Chen, Lei (Acta pharmacologica Sinica, 2017)
Sorafenib is an oral multikinase inhibitor that suppresses tumor cell proliferation and angiogenesis and promotes tumor cell apoptosis It was approved by the FDA for the treatment of advanced renal cell carcinoma in 2006, and as a unique target drug for advanced hepatocellular carcinoma （HCC） in 2007. Sorafenib can significantly extend the median survival time of patients but only by 3-5 months. Moreover, it is associated with serious adverse side effects, and drug resistance often develops. Therefore, it is of great importance to explore the mechanisms underlying sorafenib resistance and to develop individualized therapeutic strategies for coping with these problems. Recent studies to the primary resistance, mechanisms are underying the acquired resistance to sorafenib, such as crosstalk involving PI3K/Akt and JAK-STAT pathways, the activation of hypoxia-inducible pathways, and epithelial-mesenchymal transition. Here, we briefly describe the function of sorafenib, its clinical application, and the molecular mechanisms for drug resistance, especially for HCC patients.